Portuguese as a Non-Native Language at the Federal University of Espírito Santo: a brief history - Mello, Renata Rocha Vieira de (2021)
The aim of this article is to discuss the history of Portuguese as a non-native language (PNNL) at Federal University of Espírito Santo, mainly within the Languages and Literature Department and the Language Center, as well as the configurations and theoretical and methodological concepts adopted throughout the specific period of time. We noticed that the main actions of PNNL at the institution are related to the offer of courses to the community. Those courses went through significant changes regarding their organization and their concept of language(s) and language teaching, focusing on teaching and learning practices based on the concept of language-culture (MENDES, 2011, 2015, 2018), which influenced the development of courses and the use of teaching materials with an intercultural perspective. The analysis of the PNNL history at Ufes is essential to demand policies that are not restricted to courses, but that also approach teacher education and institutionalization of PNNL at the university.